(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Based on the results of the analysis carried out research, it was revealed that the natural factors, particularly the climate change, cannot significantly affect the groundwater regime in the Ararat Valley. The recorded and expected negative changes in the regime are mainly due to technogenic factors, including unsustainable use of groundwater resources for fish farming and irrigation purposes. In order to resolve the current issues and avoid more serious social-economic problems, it is necessary to initiate and implement legislative, institutional and technical comprehensive measures aimed at rational and effective use of groundwater resources in the Ararat Valley.